الأخبار الكاذبة واضطراب المجال العام الرقمي - تومي, فضيلة (جامعة الوادي - University of Eloued, 2021)
ستعالج هذه الورقة العلمية إشكالية الأخبار الكاذبة وعلاقتها باضطراب المجال العام الرقمي التي لها من الأهمية بمكان في عصرنا الحالي، خاصة ما تعلق بدوافع هذه الظاهرة وأثارها على المستوى المحلي والدولي والإقليمي وعلى المستوى العلائقي بين الأفراد والمؤسسات والدول، كما سنتطرق إلى تبيان معالم هذه الظاهرة الأخذة في النمو والاطراد الذي ولدته التقنيات الرقمية الجديدة والمزايا التي تزخر بها البيئة الرقمية. كما سنحاول تتبع هذه الظاهرة وعلاقاتها بوسائل الإعلام من جهة وبالجمهور من جهة أخرى نظرا للأهداف التي تسعى إلى تحقيقها على غرار البحث عن الإثارة وعامل الاستقطاب الذي كون لها جمهورا عريضا في البيئة الرقمية والواقعية. Abstract: This scientific paper examines a problem of fake news and its relationship to disorder of the digitized public sphere. which is of great importance in our current era, especially what is related to the motives and results of this phenomenon at the local, international and regional levels and at the level of relations between individuals, institutions and countries, and it will also address to clarify the features of this phenomenon in the growth that is generated by new digital technologies and advantages, enjoyed by the digital environment. We will also try to trace this phenomenon and its relations with the media on the one hand and with the public on the other hand, given the goals it seeks to achieve, such as the search for excitement and the factor of polarization that has created a wide audience in the digital and real environment.
العوامل والأثر
مقال
Keywords: أخبار كاذبة ; تضليل ; مجال عام رقمي ; عوامل ; أثر; fake news; misinformation; the digital public sphere; factors; impact